DevOps in IT service management: Analysis of benefits, challenges, and conditions for adoption - Cordova Urbina, Daily Ashley (2025)
Due to the growing need for rapid responses, shorter delivery cycles, and more frequent deployments is driving the emergence of DevOps, a model that complements traditional models. This study aimed to analyze the benefits and challenges of adopting DevOps in Information Technology (IT) service management processes, while also considering the organizational and technical factors that influence its implementation. Using the PRISMA methodology, a search was conducted in different databases such as Scopus, IEEE Xplore, SciencieDirect and Google Scholar, then 17 final articles were analyzed. The results indicate that implementing DevOps in IT service management benefits organizations, improving service quality and productivity by promoting continuous delivery and automation, and, above all, assisting in the software development lifecycle. However, it presents challenges: staff are not highly trained, as the concept of such implementation is confusing, and it impacts business success. Therefore, it is concluded that DevOps has improved significantly, but its long-term effectiveness depends on proper integration with governance frameworks, and more empirical research is required on its sustainability.